Diabetic Foot Ulcer Treatment Post AutoAmputation Digiti Pedis Sinistra: Case Study - Nur Azizah; Irfani Intan; Dwiyana Tulak; Muhammad Adhan Kurniawan; Titi Iswanti Afelya (Indonesian Contemporary Nursing Journal, 2019)
Introduction: Diabetes mellitus is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. According to the International Diabetes Federation, there are 425 million people suffering from diabetes in the world and will increase by 629 million in 2045. There were more than 10,276,100 cases of diabetes in Indonesia in 2017 and ranked 6 out of the top 10 countries for the number of diabetics. Diabetics have an increased risk of a number of serious health problems, one of which is the cause of foot amputation. Amputation occurs 15 times more often in diabetics than non-diabetics. Effective and comprehensive foot care can prevent the risk of ulcer becoming amputation. This study aims to provide an overview of the treatment process and the development of wounds for five weeks of treatment. Method: This study was conducted prospectively using a prospective cohort study by providing wound care to one respondent with diabetic foot ulcer for five weeks at Griya Afiat Wound Care Clinic, Makassar. Wounds were assessed using the Wound Nursing Care format from Griya Afiat Clinic. Result: the first and second week is inflammatory phase, the third to fifth week is proliferation process There is a change in the size of each wound and increasing the process of granulation and epithelialization every week of treatment until the fifth week of treatment, the wound begins to increase epithelialization and changes in wound size, especially in undermining. Conclusion: During the five weeks of treatment, the wound healing process has developed well. The wound has no potential for amputation if the wound care process is still balanced with the selection of appropriate dressings and patient compliance in performing wound care. Other factors that inhibit the wound healing process need to be known.